Ontology-Based Intelligent Control and Optimization of Ukraine's Energy System - Chernova, Natalia; Serhiienko, Olena; Ippolitova, Inna; Kaganovskyy, Oleksandr; Negliad, Andrii (My University, 2025)
Energy sector is one of the core Ukraine economy structural components, its sustainable existence determines the development vector of the society. It can be described as a complex non-linear multidimensional system, in which transient processes operate and critical and chaotic regimes emerge. The creation of an effective control scheme for such a dynamic macro system is associated with a number of problems in the field of as design so and implementation and is still the topic for scientific discussions. The paper aim is to develop a comprehensive simulation ontology-based model of the energy system of Ukraine, which can be applied as the basis for a corresponding decision-making support system. The following tasks are to be completed to achieve the mentioned goal: determination of the main structural components of the energy system, which should be reflected in the model; determination of the required level of decomposition of the above-mentioned elements; construction of the basic version of the model, assessment of adequacy, planning and conducting of relevant model experiments; obtained results analysis.
Keywords: adaptation models; analytical models; decision making; process control; ontologies; vectors; planning; transient analysis; optimization; robots